(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the implementation process and outcomes of the 5S method in managing personnel records at General Hospital No.1 Lao Cai province in 2025, and to analyze facilitators and challenges during implementation. Subjects and methods: A cross-sectional descriptive study combining quantitative and qualitative methods. Quantitative data were collected using a 5S practice checklist and existing records on personnel file management through observation and document review. Qualitative data were obtained through in-depth interviews with hospital leaders and focus group discussions with staff. Results: The implementation of 5S was carried out systematically and comprehensively. All five components (Sort, Set in order, Shine, Standardize, Sustain) achieved a “very good” level, with high mean scores ranging from 18.6-19.0. The overall score of 93.9 ± 3.9 indicated high and consistent effectiveness of 5S implementation in the records storage area Conclusion: The application of 5S contributed to improving the organization, preservation, and retrieval of personnel records. Continued supervision and reinforcement of routine practice are necessary to ensure sustainability.